(untitled) (Universal International Scientific Journal, 2026)
This scientific article analyzes the modern philosophical interpretation of educational modernization in the context of social development, globalization and the digital society. Educational modernization is considered on the basis of ontological, epistemological and axiological approaches, and its role in the development of human capital is justified. The philosophical foundations of the processes of modernization of the national education system are also revealed.